Barriers to a Circular Economy Transition for the Use of Recycled Plastics in the Textile Industry - Simões, Soraia Sofia Costa (2022)
Dissertação de Mestrado em Engenharia e Gestão Industrial apresentada à Faculdade de Ciências e Tecnologia